2015
DOI: 10.1590/0034-737x201562040010
|View full text |Cite
|
Sign up to set email alerts
|

Soil chemical properties affected by cover crops under no-tillage system

Abstract: The use of cover crops in no-tillage systems (NTS) can significantly improve the soil's fertility. Thus, a study was performed to evaluate changes in chemical properties of soil caused by cover crops in a no-tillage system. The field experiment consisted of the following crop rotation: cover crops/rice/cover crops/rice. The experimental design was in randomized blocks with three replications. Treatments consisted of four cover crops (Brachiaria brizantha(Hochst. ex A. Rich.) Stapf. cv. Marandu, Brachiaria ruzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 9 publications
0
15
1
3
Order By: Relevance
“…Nascente et al (2015) observed significant increases in soil nutrient levels, soil organic matter, cation exchange capacity, and base saturation after two years of cultivating cover crops by following rice crops. Cover crops such as grasses Panicum maximum, Brachiaria ruziziensis, and Brachiaria brizantha produce large amounts of dry biomass (> 10 Mg ha -1 ) and provide significant increases in soil fertility (Moreti et al, 2007;Rosolem et al, 2010;Pacheco et al, 2011;Nascente et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Nascente et al (2015) observed significant increases in soil nutrient levels, soil organic matter, cation exchange capacity, and base saturation after two years of cultivating cover crops by following rice crops. Cover crops such as grasses Panicum maximum, Brachiaria ruziziensis, and Brachiaria brizantha produce large amounts of dry biomass (> 10 Mg ha -1 ) and provide significant increases in soil fertility (Moreti et al, 2007;Rosolem et al, 2010;Pacheco et al, 2011;Nascente et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
“…Nascente et al (2015) observed significant increases in soil nutrient levels, soil organic matter, cation exchange capacity, and base saturation after two years of cultivating cover crops by following rice crops. Cover crops such as grasses Panicum maximum, Brachiaria ruziziensis, and Brachiaria brizantha produce large amounts of dry biomass (> 10 Mg ha -1 ) and provide significant increases in soil fertility (Moreti et al, 2007;Rosolem et al, 2010;Pacheco et al, 2011;Nascente et al, 2015). However, despite not having significant changes in the chemical and physical properties of the soil, due to the use of cover crops in our trial, this practice should be continued because, ,on the long run, it can provide cycling nutrients and other benefits such as maintenance of soil moisture, protection against erosion, and lower oscillation of soil temperature Nascente et al, 2015) and can produce grains.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations